Crnci su izdrzali, a ja? . The Black Have Endured, and I? - Juric, Zvonimir (Factum, 2001)
Duration: 00:35:00 The film is shot during Christmas time in 2000. It focuses on a group of friends and their interactions, while in the meantime also catched glimpses of the filmakers hometown and its people.